Barriers to Males Involvement in Family Planning Services in Arba Minch Town, Southern Ethiopia: Qualitative Case Study - Alemu Tamiso; Admasu Tassew; Henok Bekele; Zale Zemede; Admasu Dulla (International Journal of Public Health Science (IJPHS), 2016)
Effective utilization of family planning services are major contributors of improved maternal health. This, in turn, needs adequate involvement of male partners through direct uptake the services and approval of the spouses’ usage. Yet the family planning method utilization as well as male involvement is indicated to be low in Ethiopia. Qualitative case study was conducted in August 2015 in Arba Minch town to identify barriers to male involvement in uptake of family planning services. Open ended, semi-structured questionnaire was used to interview the participants. Four men and four women are purposively selected. Interviews were conducted in audibly private location after verbal consent was obtained from the recruited individuals. All interviews were recorded and transcribed verbatim. The narratives were then translated to English and the responses are aggregated in to nine concepts. The final aggregated data were analyzed using OpenCode 3.4 software based on thematic framework analysis. Total of eight participants (four men and four women) were interviewed where seven are married and one is single. Participants identified that, Perception (or opinion) towards family planning as women’s issue, Sex preference for inheritance and considering children as measure of blessing of and Fear of partner sexual promiscuity and to reduce women’s attractiveness were barriers for male involvement in modern family  planning method. Future interventions aimed at improving family planning services and methods utilization in Arba Minch town and similar settings need to consider these bottlenecks for male involvement.